Biology of testicular germ cell tumors. Issue 10 (October 2008) - Hussain, Syed A; Ma, Yuk Ting; Palmer, Daniel H; Hutton, Paul; Cullen, Michael H
Germ cell tumors are derived from cells of the germ cell lineage and are the most common solid malignancies to affect young Caucasian men between the ages of 15 and 40 years. All testicular germ cell tumors develop from the same precursor lesion, intratubular germ cell neoplasia unclassified, which in turn is thought to arise from malignant transformation of a primordial germ cell or gonocyte. These tumors are characterized by extreme chemosensitivity and are considered a model for curative disease. In spite of this, a small subset of patients with metastatic disease fail to achieve a complete response with cisplatin-based chemotherapy or relapse from complete remission. Understanding the molecular biology may help the design of new therapies for those patients with a poor prognosis and could also improve the treatment of cancer in general. Current understanding of the role of genetic and epigenetic factors in the etiology of germ cell tumors and the biochemical mechanisms underlying chemotherapy sensitivity and resistance is discussed in detail in this review.